Exploring the extraction capabilities of natural cyclodextrin-nanosponges: The improvement moving from α- to γ-cyclodextrin-based polymers - Nina Felli; Davide Filardi; Riccardo Sergi; Luisa Maria Migneco; Massimo Giuseppe De Cesaris; Lorenzo Antonelli; Iolanda Francolini; Alessandra Gentili (Advances in Sample Preparation)
Cyclodextrins (CD) are cyclic oligosaccharides known for their capability to form inclusion complexes with molecules of appropriate size. CDs can also be used as polyfunctional monomers in polymerization reactions to prepare specialised sorbents with characteristics of biodegradability. In this work, different CD-based polymers, known as “nanosponges” (CDNS), were obtained using natural CDs (α-, β-, and γ-CD) as monomers, citric acid as the cross-linker and sodium dihydrogen phosphate (NaH2PO4) as the catalyst. CD cross-linking was confirmed by the carbonyl band shift in IR spectroscopy and the more complex degradation pathway in CDNS compared to CDs in thermogravimetric analysis. Scanning electron microscopy evidenced a porous structure of CDNS. Their sorption properties were investigated in the dispersive-solid phase extraction of 42 model compounds (common organic contaminants including drugs, hormones, herbicides, and pesticides) from river water samples. Among all the polymers, γ-CDNS exhibited the highest efficiency, achieving recoveries averaged on all the analytes of 67% and 79% at the concentration of 0.5 and 5 µg/L, respectively. Relative standard deviations were always below 20%. Detection limits ranged from 0.001 to 0.462 µg/L, while quantitation limits from 0.004 to 1.428 µg/L. The synthesized material is easy to produce, and the developed procedure enables the analysis of 10 samples/h, opening the door to new applications in sample preparation. Finally, the application of different metrics proved the environmental compatibility of the entire analytical procedure (AGREE score=0.55, and ComplexMoGAPI score=64) and the good practicability of the extraction method proposed (BAGI score > 60).